2020
DOI: 10.21203/rs.3.rs-95379/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does the place of residence affect the achievement of exclusive breastfeeding? A study in Eastern Indonesia

Abstract: Eastern Indonesia is a region that often underperforms in the health sector. The study aims to analyze the effect of the place of residence to achieve exclusive breastfeeding in Eastern Indonesia. The study employed data from the 2017 Nutrition Status Monitoring Survey. Toddler (7-59 months) about 8,291 were sampled. Variables included were exclusive breastfeeding status, the place of residence, mother's age, mother's education level, mother's marital status, mother's employment status, toddler's age, and todd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(25 reference statements)
0
5
1
Order By: Relevance
“…The situation means that toddlers in rural areas in East Java have a higher chance of experiencing EBF. This finding is different from previous studies, which found that toddlers in urban have a higher likelihood of experiencing EBF 18 .…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The situation means that toddlers in rural areas in East Java have a higher chance of experiencing EBF. This finding is different from previous studies, which found that toddlers in urban have a higher likelihood of experiencing EBF 18 .…”
Section: Resultscontrasting
confidence: 99%
“…The condition is consistent with the results of another European multiregional review, which showed that younger, less trained mothers of toddlers were more likely to abandon breastfeeding before six months, indicating that the mother not achieved EBF. The level of schooling, parity, and social status of mothers under the age of five are all markers of high-risk under-five children who do not have EBF, according to these results [18][19][20] .…”
Section: Resultsmentioning
confidence: 99%
“…This is probably due to better information exposure about the benefits of EBF in urban areas than in rural areas. The effect of information exposure that may improve mother’s knowledge about EBF was proven as one determinant of EBF success by several studies [ 17 , 21 , 28 , 29 ]. In Indonesia, urban areas tend to have better access to health services and information than rural areas, and this leads to higher coverage of health programs [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stunted toddlers are more common in babies who are not exclusively breastfed. Thus, exclusive breastfeeding is highly recommended 18,19 .…”
Section: Table 5 Cross-tabulation Between Stunted Toddler Prevalencementioning
confidence: 99%